Acontecimientos Estresantes Presentes En Una Mujer Con Depresión Postparto Que Habita En La Localidad De Kennedy; Bogotá Colombia (2019)
In the gestational stage, the woman faces physical and psychological changes, emotional changes during pregnancy, are not consequences derived only from hormonal states, but from the external environment that surrounds the mother, involving the maternal, paternal family, the couple, and the family of the same, however also influences relations with neighbors, co-workers among others.